Role of cytokinins in seed development in pulses and oilseed crops: Current status and future perspective - Sharma, Sandhya; Kaur, Parampreet; Gaikwad, Kishor (Frontiers in Genetics, 2022)
Cytokinins constitutes a vital group of plant hormones regulating several developmental processes, including growth and cell division, and have a strong influence on grain yield. Chemically, they are the derivatives of adenine and are the most complex and diverse group of hormones affecting plant physiology. In this review, we have provided a molecular understanding of the role of cytokinins in developing seeds, with special emphasis on pulses and oilseed crops. The importance of cytokinin-responsive genes including cytokinin oxidases and dehydrogenases (CKX), isopentenyl transferase (IPT), and cytokinin-mediated genetic regulation of seed size are described in detail. In addition, cytokinin expression in germinating seeds, its biosynthesis, source-sink dynamics, cytokinin signaling, and spatial expression of cytokinin family genes in oilseeds and pulses have been discussed in context to its impact on increasing economy yields. Recently, it has been shown that manipulation of the cytokinin-responsive genes by mutation, RNA interference, or genome editing has a significant effect on seed number and/or weight in several crops. Nevertheless, the usage of cytokinins in improving crop quality and yield remains significantly underutilized. This is primarily due to the multigene control of cytokinin expression. The information summarized in this review will help the researchers in innovating newer and more efficient ways of manipulating cytokinin expression including CKX genes with the aim to improve crop production, specifically of pulses and oilseed crops.